Prosecutorial Independence Following The Decision Of The Constitutional Court Of The Republic Of Indonesia Number 6/PUU-XXII/2024 - Fitri, Icha Cahyaning (JURNAL HUKUM SEHASEN, 2025)
The position of the Attorney General's Office in the constitutional system is ambivalent because it is located on two sides of the branches of power that should be separate, namely the first branch of executive power related to the structure and flow of command that leads to the President as Head of Government, and the second branch of judicial power in the context of prosecution duties in the criminal justice system. The issue of independence will be a central issue in the positioning of the Attorney General's Office in its assignment, where structurally the Attorney General leads to the President with his prerogatives, but functionally is required to be independent and independent of any political pressure. This research is a normative research with a statutory approach, conceptual approach and comparative approach. The decision of the Indonesian Constitutional Court Number 6/PUU-XII/2024 has created a new concept of the independence of the Prosecutor's Office in the Indonesian constitutional system. The purpose of this research is to seek and find the best institutional concept for the Prosecutor's Office of the Republic of Indonesia in carrying out judicial and executive functions and duties at the same time in a balanced and transparent manner. It is expected that the institutional concept can maximize the role of the AGO in law enforcement and provide positioning of the AGO institution in the criminal justice system in Indonesia. The decision of the Constitutional Court of the Republic of Indonesia Number 6/PUU-XII/2024 has provided different constitutional interpretations and can have an impact on the institutional aspects of the Prosecutor's Office so that it can affect the law enforcement mechanism in Indonesia. This research will provide the best recommendations for the concept and vision of the Prosecutor's Office in the future.